M2A2 Problem Sheet 1 - Calculus of Variations

Solutions
1. Conservation of ’energy’. The Euler-Lagrange equation corresponding to a functional F (y, y , x) is ∂F d ∂F = 0. − ∂y dx ∂y Show that ∂F d ∂F )= (F − y . dx ∂y ∂x ∂F = constant. ∂y
d dx ( F

Hence, in the case that F is independent of x, show that F −y

Solution Evaluate the expression (

−y

∂F ∂y

) explicitly. We get:

∂ ∂ ∂ ∂F d ∂F ∂F +y +y , )F − y −y = ∂x ∂y ∂y ∂y dx ∂y ∂x

as required; the other terms on the left cancel in pairs, provided y satisfies the Euler-Lagrange equation. If ∂F ∂x is identically zero, then ∂F ) is constant. If F is the Lagrangian of a mechanical E = (F − y ∂y system, the quantity −E is called the energy. 2. The hanging rope. A rope hangs between the two points (x, y ) = (±a, 0) in a curve y = y (x), so as to minimise its potential energy
a

mgy
−a

1 + y 2 dx

while keeping its length constant:
a

1 + y 2 dx = L
−a

Of course L > 2a. Find and solve the Euler-Lagrange equation. Solution We seek to extremise the integral
a a

F dx =
−a −a

( y − λ)

1 + y 2 dx,

where λ is a Lagrange multiplier. The Euler-Lagrange equation is ∂F d ∂F − = 0, ∂y dx ∂y 1

the speed of light. while K is found from the length of the rope: a −a 1 + y 2 − ( y − λ) y2 1+y 2 = y−λ 1+y2 = K −1 . Find the leading approximation to this Lagrangian in the case ˙2 x << 1. The constant m0 is called the ’rest mass’ of the particle. ∂L = ˙i ∂x 2 ˙i m0 x 1− ˙ |2 |x c2 ˙ m0 x 1− ˙ |2 |x c2 . and λ = −K −1 cosh(Ka). 4 3. c2 Solution The ’momentum’ is ∂L = ˙ ∂x (In components. c2 Show that the equation of motion can be interpreted as Newton’s 2nd law. The relativistic particle A particle moving with speed near c.which is 1+y2 = d ( y − λ) dx y 1+y2 . cosh2 (Kx)dx = 1 sinh(2Ka) + a = L. question 1.the relativistic energy of the particle. but with a mass depending on the speed of the particlem= m0 1− ˙2 x c2 . But F is independent of x. That is. Use the result of question 1 to find a conserved quantity . has Lagrangian L = − m0 c 2 1− ˙ |2 |x − U (x). a constant. y 2 = K 2 (y − λ)2 − 1. ). and λ are found from the two boundary conditions y (±a) = 0. Here the constants x0 . giving x0 = 0. so by the result of ∂F ) is constant. . E = (F − y ∂y ( y − λ) That is Thus y = λ + K −1 cosh(K (x − x0 )). a second order ode for y .

Solution The Euler-Lagrange equation is ∂L ∂ ∂L ∂ ∂L − − = 0. the energy expands as For |x E = m0 c2 + ( m0 2 ˙ | + U (x) + O(c−2 ). x ˙i m0 x 1− ˙ |2 |x c2 m0 1− ˙ |2 |x c2 . ∂x This ’looks like’ Newton’s second law: d ∂U ˙) = − ( mx . ∂u ∂x ∂ux ∂y ∂uy 3 . Suppose u takes a specified value on the boundary ∂ Ω of Ω. d ∂L ∂L = . y )udxdy. ˙ | << c. Find the Euler-Lagrange equation for the function u(x. these are called Dirichlet boundary conditions. E=x ˙. y ) which minimises (extremises): L(ux . dt ∂x provided we set: m= The energy is given as above by ˙. where the domain of integration is a simply connected finite region Ω. y )dxdy = Ω Ω 2 F ( u2 x + uy ) + f (x. |x 2 4. u. A nonlinear Laplace equation.and so the Euler-Lagrange quation. ∂L −L= ˙i ∂x + m0 c 2 1− ˙ |2 |x + U (x) = c2 + U (x) = m0 c 2 1− ˙ |2 |x c2 mc2 + U (x). ˙ dt ∂ x ∂x is: d dt ˙ m0 x 1− ˙ |2 |x c2 =− ∂U . x. uy .

the element of arc length . using a Lagrange multiplier and the constraint x2 + y 2 = a2 . y ) − 2 ∂ ∂ 2 2 ( ux F ( u2 ( u y F ( u2 x + uy )) − 2 x + uy )) = 0. This is a helix. 4 . Find the curve which minimises this length. the more general solution goes through the same two end-points. In Cartesians. The metric . To satisfy the boundary conditions we get: z2 − z 1 (φ − φ 1 ).is given in cylindrical polars by: ds 2 = a 2 dφ 2 + d z 2 . φ1 ) and (z2 . φ2 ). which minimise the curve length with the element of arc length given by ds 2 = d x 2 + d y 2 . the ’Lagrangian’ parametrising the curve by arc length is s2 ( s1 dy dz dx 2 ) + ( )2 + ( )2 − λ(x2 + y 2 − a2 )dsdz. Write down the length of a curve on the cylinder joining the points ( z1 . ds ds ds The Euler-Lagrange equations are then: d ds dx ds dy 2 x 2 dz 2 (d ds ) + ( ds ) + ( ds ) = −2λx. z = z1 + φ 2 − φ1 z = z1 + z2 − z1 (φ − φ 1 ) φ2 − φ1 + 2nπ but because φ is multiply valued. Solution As with the problem of geodesics in the plane. Consider a circular cylinder of radius a. the solution here is that φ depends linearly on z : z = kφ + z0 . Is there more than one solution? Repeat this calculation in Cartesian coordinates. ∂x ∂y 5.This is f (x. for any integer n. Geodesics on a cylinder. whose axis is the z -axis. wrapped around the cylinder.

d2 x = −2λx. Thus x y z = a cos((s − s0 )/a). 5 . Now this is valid for any parameter s on the curve. = bs + c where we have used the constraint to fix some of the constants of integration. λ = 1/(2a2 ). But if we choose s to be the arc-length. dy 2 x 2 dz 2 (d ds ) + ( ds ) + ( ds ) = 1 . ds 2 Now. ds 2 d2 z = 0. ds 2 d2 y = −2λy . this fixes Hence. = a sin((s − s0 )/a). This is the parametric equation of a helix. dy 2 x 2 dz 2 (d ds ) + ( ds ) + ( ds ) = 0. we find λ explicitly. as before. using the constraint x2 + y 2 = a2 and its first and second derivatives.d ds and d ds dy ds dy 2 x 2 dz 2 (d ds ) + ( ds ) + ( ds ) dz ds = −2λy .